Integrating food is medicine and regenerative agriculture for planetary health - Rahman, Marcia S.; Wu, Olivia Y.; Battaglia, Kyra; Blackstone, Nicole Tichenor; Economos, Christina D.; Mozaffarian, Dariush (Frontiers in Nutrition, 2024)
The urgent need to address both human and environmental health crises has brought attention to the role of food systems in driving climate change, biodiversity loss, and diet-related diseases. This paper explores the intersection of Food is Medicine (FIM) and regenerative agriculture (RA) as an emerging approach with the potential to help address the interconnected challenges of human and ecological health within healthcare and food systems. FIM programs, such as produce prescriptions and medically tailored meals, aim to improve health outcomes by increasing access to nutritious foods and promoting nutrition equity. RA, focusing on soil health, biodiversity, and reduced reliance on synthetic inputs, offers more sustainable agricultural practices that can align with FIM goals. This paper highlights key opportunities, recent policy developments, and evidence gaps, calling for concerted efforts to clearly define RA practices and foster collaboration between community, healthcare, agriculture, and policy stakeholders. Strengthening these interconnections could lead to more resilient food systems and improved health outcomes at both individual and population levels.